PENGARUH TUMPANGSARI TERHADAP PERTUMBUHAN DAN HASIL PANEN JARAK PAGAR (Jatropha curcas L.) HASIL REHABILITASI - Sri Mulyaningsih; Budi Hariyono (BERITA BIOLOGI, 2012)
A research to study the effect of intercropping on rehabilitated of physic nut (Jatropha curcas L.) was conducted in Muktiharjo Research Station, Pati, Central of Java, from January to December 2010. Plant materials were physic nut rehabilitated by grafting of main branch with IP-2A (1 year old) and intercrops (peanut, soybean, mungbean and sesame). The experiment arranged in randomized block design with 6 replications. The treatments were: 1) intercropping peanut + physic nut, 2) intercropping soybean + physic nut, 3) intercropping mungbean + physic nut, 4) intercropping sesame + physic nut, and 5) physic nut monoculture. Plot size was 8 m x 8 m, plant distance of physic nut 2 m x 2 m, and plant distance for peanut, soybean and mungbean were 25 cm x 25 cm and sesame was 50 cm x 25 cm. The result showed that jatropha seed yield on intercropping physic nut with soybean (980.05 kg/ha) and mungbean (974.22 kg/ha) were not significantly different from physic nut monoculture (1,094.84 kg/ha). Crop that appropriate for intercropped with rehabilitated physic nut (second year) were soybean and mungbean.